If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2(x + -3) + 4 = 6x + -3(x + 2) Reorder the terms: 7x + -2(-3 + x) + 4 = 6x + -3(x + 2) 7x + (-3 * -2 + x * -2) + 4 = 6x + -3(x + 2) 7x + (6 + -2x) + 4 = 6x + -3(x + 2) Reorder the terms: 6 + 4 + 7x + -2x = 6x + -3(x + 2) Combine like terms: 6 + 4 = 10 10 + 7x + -2x = 6x + -3(x + 2) Combine like terms: 7x + -2x = 5x 10 + 5x = 6x + -3(x + 2) Reorder the terms: 10 + 5x = 6x + -3(2 + x) 10 + 5x = 6x + (2 * -3 + x * -3) 10 + 5x = 6x + (-6 + -3x) Reorder the terms: 10 + 5x = -6 + 6x + -3x Combine like terms: 6x + -3x = 3x 10 + 5x = -6 + 3x Solving 10 + 5x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10 + 5x + -3x = -6 + 3x + -3x Combine like terms: 5x + -3x = 2x 10 + 2x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 10 + 2x = -6 + 0 10 + 2x = -6 Add '-10' to each side of the equation. 10 + -10 + 2x = -6 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = -6 + -10 2x = -6 + -10 Combine like terms: -6 + -10 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 3(2-x)+3x=2(3-x)+4 | | 4-5(x-1)+3x=2x-3(2x-3) | | 2x-3(x-5)=4-2(x+4) | | 5-7x=2-9x | | 36x^3-72x^2+11x=0 | | 5y-3+y+33=6y+30-2y | | 2x+4=7x-6 | | 2m-48=6m | | 3x-7=5x+15 | | 17x^2-51x-170=0 | | 5h+6=12-h | | h=-16t^2+32t+5168 | | 4+4*5=35 | | 4b+3(b-2)=15 | | 2(4c-7)=8(c-3) | | 4ab+1-2a-2b=0 | | 0=9x^2-81 | | 22x^2-66x-616=0 | | 0=36x^2-84x+49 | | h(t)=-26t^2-32t+5 | | 64-z^6=0 | | -27=-4r-(-17) | | 14x+x=15 | | 3x^2y^4-81x^2y=0 | | 0.3(2x+7)=1.8 | | 0=-4x^2-4x-1 | | P^3q-pq=0 | | 0=3x^2-7x+4 | | 0=4x^2+4x-15 | | 0=36x^2-16 | | x^2+5=8x+14 | | 10x-4=10x+2 |